Review of the microleafhopper subgenus Matsumurasca (Solanasca) Ghauri, 1974 (Hemiptera: Cicadellidae) from Costa Rica, with description of a new species and its population dynamics in papaya crops - Arrieta-Arrieta, Luis Arturo; Pinedo-Escatel, J. Adilson; Blanco-Rodríguez, Edith; Martínez, Alejandro Vargas; Herrera, Allan González; Molina-Bravo, Ramón (Zootaxa, 2025)
The taxonomy of the microleafhopper subgenus Matsumurasca (Solanasca) Ghauri, 1974 in Costa Rica is revised. A new species, Matsumurasca (Solanasca) judokuatare Arrieta-Arrieta & Pinedo-Escatel sp. nov., is described and illustrated from Puntarenas and Limón provinces. The new species can be distinguished from other Neotropical species by the following combination of features: rounded anterior margin of crown, apex of aedeagus wide and square-shaped, gonoduct medially wide, and basal aedeagal processes slender. In addition, M. laceiba (Ross & Cunningham, 1960) and M. stevensi (Young, 1953) are reported for the first time from Costa Rica and Mexico, respectively. A key to all species of Matsumurasca known to occur in Costa Rica and a distributional map are provided. The population dynamics of the new taxon in papaya crops throughout fourteen months of monitoring is discussed.